Implementasi E-Government Berbasis Aplikasi Santer Dalam Meningkatkan Pelayanan Publik Di Kota Samarinda - Al Munawaroh; Muhammad Farid Azis; Reno Ridhoi; Tri Duwi Pramudito; Wawan Joko Pranoto (PT. ALHAFI BERKAH INDONESIA, 2023)
The Samarinda city government provides solutions related to existing problems in community services in managing administration in Samarinda City, namely through the Samarinda City Communication and Information Service, the Samarinda Integrated e-Government application (SANTER) was created. The main problems identified are obstacles to public services in Samarinda City, especially related to long administrative procedures, lack of service facilities, and the prevalence of extortion. The aim of this initiative is to increase the efficiency and transparency of public services through digital transformation using the SANTER application. Descriptive research methods with a qualitative approach were used along with data collection techniques such as in-depth interviews, participant observation, documentary research, and focus group discussions. The results of the service are in the form of e-Government with features that can be used by people from anywhere without having to come to a public administration service location. It is hoped that this application will be an effective solution for improving Samarinda City public services and improving the quality of administrative services to the city government.